2006
DOI: 10.3200/socp.146.3.349-379
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Communication: Task Performance and Satisfaction

Abstract: The author assessed satisfaction and performance on 3 tasks (idea generation, intellective, judgment) among 75 dyads (N = 150) working through 1 of 3 modes of communication (instant messaging, videoconferencing, face to face). The author based predictions on the Media Naturalness Theory (N. Kock, 2001, 2002) and on findings from past researchers (e.g., D. M. DeRosa, C. Smith, & D. A. Hantula, in press) of the interaction between tasks and media. The present author did not identify task performance differences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…This is consistent with previous researches that suggest media use differences may affect the satisfaction (Simon, [2]; Murthy & Kerr, [22]; Bates & Cleese, [35]; Olaniran, [23]. Today, most manager's routine activities will fit somewhere into a communication media at one time or another.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with previous researches that suggest media use differences may affect the satisfaction (Simon, [2]; Murthy & Kerr, [22]; Bates & Cleese, [35]; Olaniran, [23]. Today, most manager's routine activities will fit somewhere into a communication media at one time or another.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…It has already been found that participants in face-to-face teams will be more satisfied with the team experience and with the medium than participants in CMC teams [22]. Simon [2] indicated a greater preference for the medium among participants working face-to-face or through videoconferencing than among those connected through instant messaging. Also, it was found that participants in the audio condition reported lower levels of satisfaction with that medium than did those with either the text-based system or the video system [9].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, scholarly attention to IM use and effects is increasing as well. Some factors of IM as a communication technology that may affect argumentative discourse include that it is synchronous, precluding more carefully planned contributions that are possible (although not necessary) in asynchronous communication technology such as e-mail or discussion boards (Loewenstein, Morris, Chakravarti, Thompson, & Kopelman, 2005), it is perceived as informal in comparison to other communication technology (Cameron & Webster, 2005), and is associated with lower task satisfaction, but similar task performance, relative to other communication technology (Simon, 2006). Although these and other studies have investigated the uses and outcomes of IM in organizations, comparisons of argumentative discourse in IM and FtF interactions are less common in the literature.…”
Section: Communication Medium and The Structuration Of Conversationalmentioning
confidence: 99%
“…Under the right conditions, teleconference meetings can be of equal quality to face-to-face meetings and substitute some business travel [3][4][5][6]. From an organizational point of view, reasons to promote teleconference use include time and money spent on traveling [1,[7][8][9], physical and emotional toll caused by traveling [1], and greenhouse gas emissions [10].…”
Section: Introductionmentioning
confidence: 99%